Analysis of Basic and Non-Basic Sectors in Denpasar City in the middle of Covid-19 Pandemic Era - Aprilia Riszi Indah Dewi Shara (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2021)
Each region has different potential resources. These potential differences will also affect the different characteristics of the economy in each region. A typical mindset thinking Bali as a tourism center briefly provides an overview of the basic sectors found in each region, including Denpasar. Apart from the tourism potential of Denpasar, it is important to identify the basic and non-basic sectors. In the midst of the Covid-19 pandemic, it is very likely that the existing economic structure will change. The identification of basic and non-basic sectors can be used as a reference in maintaining the economy so that other superior potentials can be maximized. This study aims to: (1) analyze basic and non-basic sectors in Denpasar City, (2) analyze the multiplier effect of basic sectors in Denpasar City, and (3) analyze basic sectors in Denpasar City in the middle of Covid-19 Pandemic Era. The results show: (1) There are nine basic sectors and three non-basic sectors of the twelve economic sectors which were analyzed based on Denpasar City GRDP data during 2016-2020. (2) The value of the multiplier effect of Denpasar City is 0.31. This means that the PB value for income is 0.31, so every increase in one unit of the basic sector will result in a 0.31-fold change in income for Denpasar City. (3) The most dominant basic sector of the Denpasar City in the Covid-19 pandemic era was the Information and Communications sector.